Digital Marketing Practices and Sustainable Tourism Development Relationship Findings - Muhsin Mahdi Rebat Al-kanany (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Sustainable tourism has become a strategic priority for the hotel industry amid the global shift toward environmentally responsible practices. Specific Background: Digital transformation has strengthened the role of e-marketing as a key driver of tourism promotion, yet empirical evidence on its direct contribution to sustainable tourism development remains limited in developing contexts. Knowledge Gap: Few studies have analysed how e-marketing practices influence sustainability-oriented outcomes within hotel operations, particularly in Iraq. Aims: This study examines the relationship and effect of e-marketing on sustainable tourism development in the Baron Hotel, Karbala. Results: Using data from 20 respondents and SPSS-based analyses, the study found a significant positive correlation (r = 0.530) between e-marketing and sustainable tourism development, and a statistically significant effect (p < 0.05), confirming both hypotheses. Novelty: The research offers one of the earliest empirical assessments linking e-marketing characteristics—such as digital communication, online promotion, and service personalization—to sustainability dimensions in the Iraqi hotel sector. Implications: Findings underscore the need for hotels to strengthen digital marketing strategies to enhance environmental awareness, improve visitor engagement, and support long-term sustainable tourism goals through efficient and targeted digital communication.Highlight : Highlights the linkage between e-marketing and the strengthening of sustainable tourism practices. Emphasizes the role of digital tools in enhancing tourist engagement and awareness. Underscores the contribution of e-marketing to efficient promotion and the achievement of sustainability goals. Keywords : E-marketing, Sustainable Tourism Development, Baron Hotel, Digital Promotion, Customer Awareness